2011
DOI: 10.1095/biolreprod.110.088641
|View full text |Cite
|
Sign up to set email alerts
|

Pathway for the Movement of Water and Cryoprotectants in Bovine Oocytes and Embryos1

Abstract: The permeability of cells is important for cryopreservation. Previously, we showed in mice that the permeability to water and cryoprotectants of oocytes and embryos at early cleavage stages (early embryos) is low because these molecules move across the plasma membrane predominantly by simple diffusion through the lipid bilayer, whereas permeability of morulae and blastocysts is high because of a water channel, aquaporin 3 (AQP3). In this study, we examined the pathways for the movement of water and cryoprotect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 27 publications
5
69
2
Order By: Relevance
“…This suggests that cryoprotectants permeate mouse embryos through different pathways, which depend not only on the developmental stage, but also on the cryoprotectant itself. Similar results were obtained in bovine oocytes and embryos, although species specificity does exist [15]; the permeability of embryos to water, glycerol, and ethylene glycol increased markedly at the morula stage, whereas that to acetamide, DMSO, and propylene glycol did not. Two pathways have been described for the movement of water and cryoprotectants across the plasma membrane.…”
Section: Introductionsupporting
confidence: 79%
See 4 more Smart Citations
“…This suggests that cryoprotectants permeate mouse embryos through different pathways, which depend not only on the developmental stage, but also on the cryoprotectant itself. Similar results were obtained in bovine oocytes and embryos, although species specificity does exist [15]; the permeability of embryos to water, glycerol, and ethylene glycol increased markedly at the morula stage, whereas that to acetamide, DMSO, and propylene glycol did not. Two pathways have been described for the movement of water and cryoprotectants across the plasma membrane.…”
Section: Introductionsupporting
confidence: 79%
“…We previously suggested that the permeability of mouse and bovine embryos to water and cryoprotectants increased markedly at the morula stage and that this increased permeability affected the conditions suitable for cryopreservation [13][14][15]. We showed that aquaporin 3 played an important role in this increased permeability [13][14][15].…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations